Influence of Rice Seed Replanting Growth (Oryza sativa L.) Inpari-4 Varieties with Giving Frequency of Sound Waves - Bahtiar, Bahtiar; Widodo, Chomsin S.; Santoso, Didik R. (Natural B, Journal of Health and Environmental Sciences, 2015)
Has done research that aims to examine the influence of sound wave frequency of rice seeds of the shoots phase. Rice seeds Inpari-4 varieties planted at four growing medium in the sterofoam box with the treatment of the different frequncies of 10 Hz, 4 kHz, 7 kHz, 30 kHz and one growing medium without sound treatment which serves as the control plants. Â The test parameters were often observed as an indicator of plant, a lot of leaves, wet and dry weight of roots, root lenght, moisture content and test unison is growing. The result showed that there is a sound wave frequency value responded well by rice seed shoots in the process so that its growth into the optimal frequency of 4 kHz.Â